Assessing Railway Accident Risk Through Event Tree Analysis - Mustafa Khalid, Nur Izyan; Najdi, Nur Farah Najeeha; Khairul Adlee, Nurul Faziera; Misiran, Masnita; Sapiri, Hasimah (AIP Publishing, 2019)
Railway safety is an important issue since the safety of passengers, employees, road users and residents in the area of railway can be affected when railway accidents happen. However in Malaysia, the risk management for railway safety is still new, thus few studies available in the literature. In this study, measurement models involving descriptive analysis and event tree analysis for Keretapi Tanah Melayu Berhad (KTMB)’s railway accident risk are developed by considering the primary and secondary data from KTMB. The finding shows collective risk of 0.2406, in which a strong 0.217 is influenced by human error of not following the predetermined standard operating procedures, and only 0.0232 of this risk is caused by the systematic failure. The determinant factors of such accidents include carelessness, conductor’s effect, mechanical failure, high speed, human negligent, and track’s obstruction